Alteration in the large-scale circulation of south america triggered by the upper-tropospheric cyclonic vortices of Northeast Brazil - Lyra, Matheus José Arruda; Arraut, Josefina Moraes; de Souza, Enio Pereira (Dynamics of atmospheres and oceans, 2025)
This study investigates how Upper-Tropospheric Cyclonic Vortices (UTCVs), which commonly form over Northeast Brazil (NEB), influence large-scale moisture transport across South America. UTCVs are the most important weather systems occurring in the pre-rainy season in Northeast Brazil and their understanding provides insights for improving short-term weather forecasting. Using 20 years of ERA-Interim reanalysis data (1999–2018) provided by the European Centre for Medium-Range Weather Forecasts (ECMWF) and GOES satellite imagery, we analyze circulation changes associated with UTCVs and their impacts on rainfall in NEB. Results show that while moisture typically enters South America from the tropical Atlantic and moves westward into the Amazon, approximately 36 % of UTCVs disrupted this pattern by inducing a west-to-east moisture flow from the Amazon toward NEB. These events led to enhanced convergence over the vortex region and significantly increased precipitation. We present a conceptual model summarizing these mechanisms, providing new insights into the hydrometeorological role of UTCVs in regional rainfall variability and forecasting. •Approximately 36% of UTCVs redirected moisture from the Amazon to Northeast Brazil, altering the typical flow.•Atlantic and Amazonian moisture interaction intensified convergence and rainfall over the UTCV region.•UTCVs affected continental circulation, showing features comparable to monsoon dynamics.•The study reveals how UTCVs modulate large-scale moisture transport across South America.